2014
DOI: 10.2147/ijn.s54911
|View full text |Cite|
|
Sign up to set email alerts
|

Anacardic acid enhances the anticancer activity of liposomal mitoxantrone towards melanoma cell lines – in vitro studies

Abstract: This paper describes a novel formulation of antineoplastic drug: mitoxantrone loaded into liposomal carriers enriched with encapsulated anacardic acid in the liposomal bilayer using a vitamin C gradient. Anacardic acid is a potent epigenetic agent with anticancer activity. This is the first liposomal formulation to combine an actively encapsulated drug and anacardic acid. The liposomes were characterized in terms of basic parameters, such as size, zeta potential, optimal drug-to-lipid ratio, loading time and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…The biological effects of compounds isolated from A. occidentale cashew nut bark oil have been widely evaluated and have indicated that these substances reduce and induce cell death in tumor cells such as in the breasts, kidneys, prostate, colon, lungs, and melanomas (Huang et al 2010;Hemshekhar et al 2012;Seong et al 2013;Legut et al 2014). The mechanism by which these substances present anti-tumor potential is by inhibiting histone acetyltransferase p300, which acts on DNA transcription (Balasubramanyam et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects of compounds isolated from A. occidentale cashew nut bark oil have been widely evaluated and have indicated that these substances reduce and induce cell death in tumor cells such as in the breasts, kidneys, prostate, colon, lungs, and melanomas (Huang et al 2010;Hemshekhar et al 2012;Seong et al 2013;Legut et al 2014). The mechanism by which these substances present anti-tumor potential is by inhibiting histone acetyltransferase p300, which acts on DNA transcription (Balasubramanyam et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These delivery methods include dendrimers, nanogels, nanoparticles, and liposomes, and the diversity among them provide tailor made properties for different malignancy types. Liposomal carriers with encapsulated anacardic acid (epigenetic drug) in the liposomal bilayer with a vitamin C gradient, loaded with mitoxantrone has been developed 159 . The efficacy of N-isopropylacrylamide (NIPAM)-based biodegradable nanogels with decitabine was shown in drug resistant solid tumors and leukemia cells.…”
Section: Novel Small Molecule Inhibitor Targets Of Signaling Molecmentioning
confidence: 99%
“…This could include delivering nucleic acids such as RNA sequences which work through epigenetic mechanisms. A novel formulation involving enriched liposomal carriers with encapsulated anacardic acid in the liposomal bilayer with a vitamin C gradient, loaded with mitoxantrone has been developed [77]. The epigenetic agent is the anacardic acid which has been shown to have anticancer properties.…”
Section: Delivery Of Epigenetic Drugsmentioning
confidence: 99%
“…The cytotoxicity of mitoxantrone was shown to be enhanced by the anacardic acid and the vitamin C when used on human melanoma cell lines A375 and Hs294T. However, these same two compounds – anacardic acid and vitamin C – were cytoprotective when used on a normal human fibroblast line [77]. …”
Section: Delivery Of Epigenetic Drugsmentioning
confidence: 99%